Diagnostic quality in rural health centres in Burkina Faso - Krause, Gérard; Schleiermacher, D.; Borchert, Matthias; Benzler, Justus; Heinmüller, Rolf; Ouattara, K.; Coulibaly, S.; Diasso, I.; Ilboudo, A.; Diesfeld, Hans J. (Tropical medicine & international health, 1998)
objective To study the quality of diagnostic practice in rural Burkina Faso. method In 9 health centres of 3 districts, 313 outpatient consultations were observed, and 417 diagnoses by 15 nurses were analysed. Criteria for evaluation of patient history and clinical examination were based on the diagnostic guidelines distributed by the Ministry of Health. results In only 20% of the diagnoses the nurses took a sufficient history and in only 40% they conducted a sufficient clinical examination. In 21% patients underwent no clinical examination at all. Only 12% of all diagnoses were based on sufficient history-taking and adequate clinical examinations. The individual elements of clinical examination were performed correctly in 82% of cases. The variation between nurses was immense, but no correlation could be found with regard to their basic training. However, nurses who had received the diagnostic guidelines examined patients more carefully than those who had not. Larger numbers of patients per day are not associated with shorter nurse-patient contact, and neither is sufficiency of patient history associated with duration of the consultation. conclusion The low diagnostic quality of the outpatient consultations in the studied area indicates that this issue has been neglected in national public health initiatives. But examination skills are good and diagnostic guidelines may have had a positive effect on the diagnostic quality.